Tinjauan Yuridis Pencabutan Hak Kewarganegaraan Mantan Anggota Organisasi Militan Ekstremis (ISIS) Perspektif Hukum Internasional dan Aturan Kewarganegaraan - Abdullah Raden Aji Haqqi; Rohmad Adi Yulianto; Damrah Mamang (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2021)
Citizenship is a legal bond between a person and a country. Citizenship gives people an identity. According to the Universal Declaration of Human Rights affirms that